2023
DOI: 10.3389/fpls.2023.1182461
|View full text |Cite
|
Sign up to set email alerts
|

Drought-triggered leaf transcriptional responses disclose key molecular pathways underlying leaf water use efficiency in sugarcane (Saccharum spp.)

Abstract: Drought is a major constraint to sugarcane (Saccharum spp.) production and improving the water use efficiency (WUE) is a critical trait for the sustainability of this bioenergy crop. The molecular mechanism underlying WUE remains underexplored in sugarcane. Here, we investigated the drought-triggered physiological and transcriptional responses of two sugarcane cultivars contrasting for drought tolerance, ‘IACSP97-7065’ (sensitive) and ‘IACSP94-2094’ (tolerant). After 21 days without irrigation (DWI), only ‘IAC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 84 publications
(121 reference statements)
0
0
0
Order By: Relevance
“…In this work, we demonstrated that genes involved in the photosynthesis pathway are also possible candidates for generating higher water use efficiency in plants due to their capabilities in maintaining photosynthesis during stress. Similarly, a recent study in sugarcane compared drought-sensitive and drought-tolerant varieties, with the latter presenting a superior water use efficiency and significant differences in the expression of genes related to photosynthesis, reinforcing the hypothesis that photosynthesis-related genes are good candidates for water-deficit tolerance [52].…”
Section: Gas Exchangementioning
confidence: 72%
“…In this work, we demonstrated that genes involved in the photosynthesis pathway are also possible candidates for generating higher water use efficiency in plants due to their capabilities in maintaining photosynthesis during stress. Similarly, a recent study in sugarcane compared drought-sensitive and drought-tolerant varieties, with the latter presenting a superior water use efficiency and significant differences in the expression of genes related to photosynthesis, reinforcing the hypothesis that photosynthesis-related genes are good candidates for water-deficit tolerance [52].…”
Section: Gas Exchangementioning
confidence: 72%
“…Tayade et al (2020) have shown a yield reduction in WPet between 100% and 50%. In cultivar studies (Coelho et al, 2018;Santos et al, 2019;Contiliani et al, 2023), an increase in water productivity has been observed between the interaction of deficit irrigation and sugarcane cultivar. The development of cultivars adapted to dry conditions is a more definitive method for increasing the water productivity of sugarcane compared to water-saving irrigation scenarios.…”
Section: Irrigation Management Scenariosmentioning
confidence: 99%